SOCIAL RESPONSIBILITY PERGURUAN TINGGI ISLAM DALAM MASYARAKAT HETEROGEN DI KOTA PALOPO - S, Zainuddin (PALITA, 2016)
AbstractSocial Responsibility Islamic college in a heterogeneous society is significant where thereare various permaslahan ranging from social, religious, cultural, ethnic, and so on.Implementation of social responsibility programs implemented by IAIN college Palopo in thethe form of community service programs through research and community empowerment as aPortion of Tridharma college. Various problems and constraints faced by IAIN Palopo is the lackin cooperation with the government, the lack of coordination of the implementation ofactivities, disseminate the results of research which is still low, the lack of real informationregarding the condition of society, the implementation of the work program based onindividual initiative, work programs aimed at specific groups, and there has been no workprogram, appropriate and sustainable for society.